Mass spectrometry based identification of galectin-3 interacting proteins potentially involved in lung melanoma metastasis - Dange, Manohar C.; Bhonsle, Hemangi S.; Godbole, Rashmi K.; More, Shyam K.; Bane, Sanjay M.; Kulkarni, Mahesh J.; Kalraiya, Rajiv D. (Molecular Biosystems, 2017)
Adhesive interactions between molecules on tumor cells and those on target organs play a key role in organ specific metastasis. Poly-N-acetyl-lactosamine (polyLacNAc) substituted N-oligosaccharides on melanoma cell surface glycoproteins promote lung specific metastasis via galectin-3 by facilitating their arrest and extravasation. This study reports the identification and characterization of galectin-3 interacting proteins using a combination of galectin-3 sepharose affinity and leucoagglutinating phytohemagglutinin (L-PHA) columns. A total of 83 proteins were identified as galectin-3 interacting glycoproteins, of which 35 were constituents of the L-PHA bound fraction, suggesting that these proteins carry polyLacNAc substituted beta 1,6 branched N-glycans. The identities of some of these proteins, like LAMP-1, LAMP-3, basigin, embigin, and alpha 5 and beta 1 Integrin, have been confirmed by western blotting, and functional relevance with respect to metastatic properties has been established.